(3GdSYGOI GdCHOjI aj GdJYQja HeTGgjQ GdMVQI GdeQGcTjIs - (3eMeO Hf eMeO Hf YHO Gddg, GHf GdehbJ GdeQGcTj,J (B1369 (3g` s
(3ChdgG (B:s
(3MeOkG def Rjf cd HdO HNGUI YHjOI s
(3GdfSNI HgG MhGTs
(3QJHg Ydi ebOeI hebUO hNGJeI hYdjgG HYV GdJYbOjGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B84s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B154 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs